Paradigm Transformation of Global Health Data Regulation: Challenges in Governance and Human Rights Protection of Cross-Border Data Flows - Xia L; Cao Z; Zhao Y (Risk Management and Healthcare Policy)
Linhua Xia,1 Zhen Cao,2 Yue Zhao3 1School of Economics, Shenzhen Polytechnic University, Shenzhen, Guangdong, People’s Republic of China; 2School of Law, Hainan University, Haikou, Hainan, People’s Republic of China; 3School of Law, Hainan Normal University, Haikou, Hainan People’s Republic of ChinaCorrespondence: Yue Zhao, School of Law, Hainan Normal University, Haikou, Hainan, People’s Republic of China, Email lawzy@hainnu.edu.cnAbstract: The growing global exchange of healthcare data requires more cohesive and effective regulatory frameworks to ensure fair access and protect patient privacy. However, cross-border regulatory rules for healthcare data diverge across countries, such as the EU, which highlights personal data rights and restricts cross-border flow of healthcare data through the GDPR, the United States, which emphasizes the free flow of healthcare data trade or services, and China, which emphasizes cross-border regulatory rules for healthcare data at the level of national data security. Such inconsistent policies often impede international medical research collaborations, undermine the effectiveness of telemedicine, and create barriers for healthcare providers to share patient information. Documents containing national human rights laws, the Global Initiative on Digital Health and the Global Digital Compact, which advocate for cooperation and behavioral co-regulation of healthcare data stakeholders to achieve the strategic goal of putting people at the center of healthcare, provide new ideas for solving the problem. Based on an exploration of these challenges, this paper proposes a harmonized, human rights-based approach that in turn bridges regulatory gaps and ensures data security, privacy, and accessibility in all countries.Keywords: cross-border data flow, healthcare data, regulation, human rights, safety